2015
DOI: 10.1093/nar/gkv026
|View full text |Cite
|
Sign up to set email alerts
|

ZBTB2 increases PDK4 expression by transcriptional repression of RelA/p65

Abstract: The NF-κB is found in almost all animal cell types and is involved in a myriad of cellular responses. Aberrant expression of NF-κB has been linked to cancer, inflammatory diseases and improper development. Little is known about transcriptional regulation of the NF-κB family member gene RelA/p65. Sp1 plays a key role in the expression of the RelA/p65 gene. ZBTB2 represses transcription of the gene by inhibiting Sp1 binding to a Sp1-binding GC-box in the RelA/p65 proximal promoter (bp, −31 to −21). Moreover, rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Despite conflicting evidence defining the role of PDK4 in tumorigenesis, either promoting (2, 33) or repressing carcinogenesis (3, 4); it is certain that PDK4 is an important factor to be considered in tumorigenesis. Hepatic PDK4 expression is regulated by insulin, fatty acids and hormone receptors (3436).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite conflicting evidence defining the role of PDK4 in tumorigenesis, either promoting (2, 33) or repressing carcinogenesis (3, 4); it is certain that PDK4 is an important factor to be considered in tumorigenesis. Hepatic PDK4 expression is regulated by insulin, fatty acids and hormone receptors (3436).…”
Section: Discussionmentioning
confidence: 99%
“…The PDK4 gene encodes for the PDK4 protein within the mitochondria and has recently been linked to tumor proliferation due to its function in glucose metabolic pathways (2). Several types of cancers exhibited low expression of PDK4.…”
Section: Introductionmentioning
confidence: 99%
“…However, these genes are all among the subset of genes whose expression goes up rather than down in the Zbtb2 KO, raising the question through which exact mechanisms ZBTB2 regulates gene expression. Previous studies have identified interactions between ZBTB2 and co‐activator or co‐repressor complexes containing histone acetyltransferase or deacetyltransferase activity, respectively, leading to gene activation or gene repression . In addition, ZBTB2 has been reported to interact with numerous other proteins, such as OCT4 and PTIP .…”
Section: Resultsmentioning
confidence: 99%
“…Although the regulation of p65 nuclear translocation has been extensively studied, the transcriptional regulation of p65 is poorly understood 32 . p65 transcription is known to be activated by Sp1 33 and repressed by zinc finger and BTB domain containing 2 (ZBTB2) 34 . Our study found that KLF14 inhibited NF-κB reporter luciferase and this effect was abolished by IκBα phosphorylation inhibitors, indicating that the inhibition took place upstreaming of p65 nuclear translocation.…”
Section: Discussionmentioning
confidence: 99%